Qualitative techniques for workplace data analysis - Gupta, Manish (Computer scientist); Shaheen, Musarrat 1979-; Prathap Reddy, K. (IGI Global, 2019)
"This book addresses the difficulties and challenges of selecting and applying a qualitative technique. It explores what measures should be adopted to ensure the credibility and dependability of the qualitative findings in workplace. Six key techniques namely thematic analysis, phenomenological analysis, content analysis, narrative analysis, grounded theory, and case study analysis are discussed"...